Validation of a lateral flow immunochromatographic assay for tinea unguium diagnosis. Issue 5 (8th March 2021) - Tsuboi, Ryoji; Mochizuki, Takashi; Ito, Haruo; Kawano, Shiomi; Suzuki, Yosuke; Naka, Wataru; Hata, Yasuki; Hamaguchi, Taizo; Maruyama, Ryuji
Abstract: Tinea unguium is a common nail disease caused by dermatophytes. Although direct potassium hydroxide (KOH) microscopy and fungal culture are considered the gold standard for diagnosing this disease, their accuracy is insufficient. A lateral flow immunochromatographic assay (LFIA) kit, using a monoclonal antibody against Trichophyton rubrum, was developed and its sensitivity was recently improved 50% in vitro relative to its earlier version. The present study aimed to validate the clinical utility of this improved LFIA kit for diagnosing tinea unguium in comparison with direct KOH microscopy. A similar trial was simultaneously performed using scale samples from patients with tinea pedis to determine the assay's diagnostic potential. Nail samples, approximately 2 mg in weight, were collected from 112 non‐treated tinea unguium patients and 56 non‐tinea unguium patients. Samples from 25 tinea pedis patients and 20 non‐tinea pedis patients were also collected. The sensitivity and specificity of the LFIA kit for tinea unguium was 84.8% (95/112) (95% confidence interval [CI], 76.8–90.9) and 83.9% (47/56) (95% CI, 71.7–92.4), respectively. The inconsistency rate was 15.5% (26/168) (95% CI, 10.4–21.9). The sensitivity and specificity of the LFIA kit for tinea pedis was 84.0% (21/25) and 100.0% (20/20), respectively. These results suggest that for diagnosing tinea unguium, the LFIA kit is a useful supplement to, but not a replacement for, direct KOH microscopy. For definitive diagnosis of suspected cases, appropriate sampling, repeated examinations, and a combination of diagnostic techniques are essential.